Perceptions and experiences of intrusive behavior and stalking within a culture - Sheridan, Lorraine (Psychology, crime & law, 2019)
Previous studies have compared perceptions and experiences of intrusive activity and stalking between countries and the present work compares subcultures within a single country. Singaporean women (89 Chinese, 69 Indian and 68 Malay) with similar age profiles completed a modified version of the ‘Stalking: International perceptions and prevalence’ questionnaire (SIPPQ). This contained measures of individual perceptions and experiences of a range of 47 intrusive behaviors, and a measure of stalking. Between the three ethnic groups, few differences were found in terms of how unacceptable the 47 intrusive acts were judged to be. The small number of differences identified related to courtship behaviors. Women across ethnicities reported largely the same experiences of intrusive behaviors, differing on just two of the 47 behaviors. This suggests that overarching national attitudes towards women are better determinants of the types of intrusive behaviors they are likely to experience, as opposed to their subculture. Finally, no differences were found in stalking rates between the three ethnic groups, but the overall stalking rate within the sample was high at 54.9%. This finding may provide impetus to increase awareness of stalking in Singapore, given that it was only recently criminalized in the sovereign city-state.